The European Union : readings on the theory and practice of European integration - Nelsen, Brent F.; Stubb, Alexander C-G. (Boulder, Colo. : L. Rienner, 1994)
"Dinan's book - written in an accessible, straightforward style - explains clearly the extent of European integration since World War II." "Part 1 explores the European Community's history and political developments since the early 1950s, including the emergence of the European Union in the early 1990s. Part 2 describes and analyses EC and EU institutions. Part 3 assesses the Community's policies and programs, from agriculture to industry, from social affairs to science and technology." "Imaginative and interdisciplinary in approach, the book makes the EU comprehensible and whets the appetite for further research. It is essential reading for all who are interested in the emerging New Europe."--Jacket.
The tragedy of Europe / Winston S. Churchill -- The Schuman Declaration / Robert Schuman -- Preambles to the Treaties of Rome -- A ferment of change / Jean Monnet -- A concert of European states / Charles de Gaulle -- Preamble to the Single European Act -- A family of nations / Margaret Thatcher -- A necessary union / Jacques Delors -- Preamble to the Treaty on European Union (the Maastricht Treaty) -- Altiero Spinelli and the strategy for the United States of Europe / Sergio Pistone -- A working peace system / David Mitrany -- Political integration : definitions and hypotheses / Leon N. Lindberg -- Neofunctionalism : a case of mistaken identity / A.J.R. Groom -- The theory of economic integration : an introduction / Bela Balassa -- Domestic politics and European Community policy making / Simon Bulmer -- Political elites, popular indifference and community building / Martin Slater -- Organized interests and the Europe of 1992 / Philippe C. Schmitter and Wolfgang Streeck -- 1992 : recasting the European bargain / Wayne Sandholtz and John Zysman -- Negotiating the Single European Act : national interests and conventional statecraft in the European Community / Andrew Moravcsik -- Institutional change in Europe in the 1980s / Robert O. Keohane and Stanley Hoffmann -- Choosing union : monetary politics and Maastricht / Wayne Sandholtz.
Includes bibliographical references and index.
Keywords: European Economic Community; European Union; European federation; Integration; Europe -- Economic integration; European Union countries; Economic integration; Europe